ANÁLISIS ESTRUCTURAL AL NORESTE DEL VOLCÁN NEVADO DEL RUÍZ, COLOMBIA – APORTE A LA EXPLORACIÓN GEOTÉRMICA (2012)
The structural geology studies around the Nevado del Ruiz Volcano (NRV), based on aerial photographs anddigital terrene models interpretation, in conjunction with analysis of morphological, tectonic features, striatedfault planes data and stress field calculation allow to propose a structural scheme that explains the pattern oflocation of hot springs and fluid released in the western part of the NRV. Structures and kinematics in the regionare closely related to the dominant tectonic features of the NVR, nominally longitudinal NE-SW and N-Sfaults (Palestina, Santa Rosa and San Jerónimo) and a transverse NW-SE to E-W system (Villamaría-Termales,Campoalegrito, San Ramón faults). Quaternary stress tensor was obtained with a WSW-ENE direction ofcontraction, and dextral strike slip deformation by simple shear along main longitudinal faults, while left lateraldisplacement is transmitted to most of the NW transverse structures. A WSW-ENE direction of compressionwas also calculated from striated planes of Cretaceous-Paleocene and older rocks, meaning previous rightlateral displacements along longitudinal faults (i.e. Palestina or San Jerónimo). Keywords: Nevado del Ruiz Volcano, Palestina Fault, Villamaría-Termales Fault, Stress regime, Geothermalexploration